G(0)/G(1) Switch Gene 2 Regulates Cardiac Lipolysis - Heier, Christoph (J Biol Chem, 2015)
The anabolism and catabolism of myocardial triacylglycerol (TAG) stores are important processes for normal cardiac function. TAG synthesis detoxifies and stockpiles fatty acids to prevent lipotoxicity, whereas TAG hydrolysis (lipolysis) remobilizes fatty acids from endogenous storage pools as energy substrates, signaling molecules, or precursors for complex lipids. This study focused on the role of G(0)/G(1) switch 2 (G0S2) protein, which was previously shown to inhibit the principal TAG hydrolase adipose triglyceride lipase (ATGL), in the regulation of cardiac lipolysis. Using wild-type and mutant mice, we show the following: (i) G0S2 is expressed in the heart and regulated by the nutritional status with highest expression levels after re-feeding. (ii) Cardiac-specific overexpression of G0S2 inhibits cardiac lipolysis by direct protein-protein interaction with ATGL. This leads to severe cardiac steatosis. The steatotic hearts caused by G0S2 overexpression are less prone to fibrotic remodeling or cardiac dysfunction than hearts with a lipolytic defect due to ATGL deficiency. (iii) Conversely to the phenotype of transgenic mice, G0S2 deficiency results in a de-repression of cardiac lipolysis and decreased cardiac TAG content. We conclude that G0S2 acts as a potent ATGL inhibitor in the heart modulating cardiac substrate utilization by regulating cardiac lipolysis.